SCATTER SEARCH ALGORITHM FOR HETEROGENEOUS FLEET VEHICLE ROUTING PROBLEM WITH TIME WINDOWS AND LOADING COST - Yodwangjai, Sirichai; Khammuang, Kwanniti (Life Sciences and Environment Journal, 2020)
The Vehicle Routing Problem (VRP) is one of the main problems in the fields of logistics operation management. Most VRP variants aim to minimize the total cost which includes fixed and variable costs. In some practical situations, the weight of goods is one of the constraints which has impacts in the overall cost of transportation. This issue implies another cost relating to the weight of goods referred to as the loading cost. This paper studies a heterogeneous VRP with time window constraints and loading cost consideration. A family of scatter search (SS) algorithms with the 3-Opt/Opt* local search improvement method is proposed. Besides the well-known local search, Sequencing by Loading Cost (SLC) and a new heuristic, Insertion by Loading Cost (ILC) method are also augmented with 3-Opt/Opt* and investigated. Computational experiments of the algorithms with benchmark problems is conducted. The results show that enhancing 3-Opt/Opt* with SLC and ILS benefits the quality of the solutions.